Interfacial shear strength of flax fibers in thermoset resins evaluated via tensile tests of UD composites. - Sparnins, E.; Nyström, B.; Andersons, J.
A method of interfacial shear strength evaluation, based on the length distribution of fibers pulled out from the tensile fracture surface of an oriented flax-reinforced composite, is applied to composites with vinyl ester and acrylated epoxidized soy oil resin matrices. Two approaches for characterizing the strength of fibers with modified Weibull distribution, fiber fragmentation tests and fiber tension tests, are compared in the analysis of pull-out data. Interfacial shear strength is found to increase by a few percent when loading rate is increased from 1.33 percent to 8 percent/min.
Keywords: FLAX FIBERS; INTERFACIAL SHEAR STRENGTH; POLYMER MATRIX COMPOSITE